Analysis of Surface Wave Attenuation in Mangrove Forests - Safwan Hadi; Hamzah Latief; Muliddin Muliddin (Journal of Engineering and Technological Sciences, 2003)
This paper presents an analytical study on surface wave attenuation in mangrove forest using analytical model developed by Massel et.al. (1999). The energy dissipation in the frequency domain is determined by treating the mangrove forest as a random media with certain characteristics using the geometry of mangrove trunks and their locations. Initial nonlinear governing equations are linearized using the concept of minimalization in the stochastic sense and interactions between mangrove trunks and roots have been introduced through the modification of the drag coefficients. To see the effectiveness of the mangrove forest in attenuating wave energy the analytical model was applied to two types of mangrove forest i.e. Rhizophora and Ceriops forests. The resulting rate of wave energy attenuation depends strongly on the density of the mangrove forest, and on diameter of mangrove roots and trunks. More effective wave energy attenuation is shown by Rhizophora.